Design of photo-detector circuit for fiber optical sensor / Nurul Iliana Bakhari - Bakhari, Nurul Iliana (2012)
The optical sensor might utilize visible light, infrared, LED or laser to propagate communication data. The light ray was then sent to any light detection and conversion devices. In this project, we use photodiode to analyze the light signal rather than optical spectrum analyser (OSA). Thus, InGaAs and Si photodiode was employed to investigate the suitable driving circuit for producing smooth desired output from the sensors. The converted light signal to electrical signal was then amplified where both characteristics of both photodiodes are essentially taken care to ensure their driving circuits are workable. Several calculations were made to select the parameters' values. The findings revealed Silicon photodiode results were comparable between simulation and measurement. However, the results from InGaAs photodiode produce lower gain from the theory. In addition, InGaAs photo detection configuration is simpler than the Silicon circuitry.